Microstructural analysis of highly active cathode material La0.7Sr0.3Ti0.15Fe0.65Ni0.2O3-δ (LSTFN) by optimizing different processing parameters. Issue 8 (15th April 2021) - Hanif, Muhammad Bilal; Gao, Jiu-Tao; qayyum, Sana; Shaheen, Kausar; Wang, Yue-Peng; Yasir, Muhammad; Li, Chang-Jiu; Li, Cheng-Xin
Abstract: The modified Pechini method was applied to prepare a highly active and novel cathode material La0.7 Sr0.3 Ti0.15 Fe0.65 Ni0.2 O3-δ (LSTFN). This material was coated on the LGSM electrolyte through a screen-printing technique with variable thicknesses of 28 ± 8, 41 ± 8, and 62 ± 8 μm, respectively. Different fabrication parameters, including sintering temperature, time, coating thickness, and variations in ball-milling, which affect the electrochemical performance of the cathode material, were investigated. X-ray diffraction analysis of the cathode material suggested that it exhibits a cubic crystal structure with a LSTFN single phase. The morphological studies were conducted using scanning electron microscopy (SEM), which confirmed that the electrode material had a highly porous structure. Meanwhile, the electrochemical properties of the material were studied by electrochemical impedance spectroscopy (EIS), which revealed that by varying different parameters, the electrochemical performance of the electrode material was enhanced. The coated cathode materials with variable thicknesses were analyzed at different sintering temperatures and times. Experimental results suggest that the optimum sintering temperature and time were 950 °C and 3 h, respectively, at which LSTFN exhibits the minimum polarization resistance (RP ) of 0.046 Ωcm 2 when sintered at 800 °C for 3 h.